2012
DOI: 10.1038/ejhg.2011.224
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of family medical history with personal genome screening for risk assessment of common cancers

Abstract: Family history-based risk assessment (FHRA) is a genetic tool for identifying those at risk of disease. Genome-wide association studies have shown that single nucleotide polymorphisms (SNP) are statistically associated with low-to moderate-level risks of diseases. There has been limited study of complementarity for these two assessment methods. We sought to compare cancer risk categorizations from FHRA and from Navigenics Personal Genome Screening (PGS). We compared FHRA with PGS for breast (22 females), prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…The results of our study are consistent with those found by Heald et al, 14 which reported poor concordance between risk assessment methods for three conditions tested in Navigenics PGT (breast cancer, prostate cancer, and colon cancer). We expand on their work by analyzing more conditions included in the PGT panel and in a larger sample of individuals.…”
Section: Family and Medical History Assessments: Other Potential Genesupporting
confidence: 92%
See 1 more Smart Citation
“…The results of our study are consistent with those found by Heald et al, 14 which reported poor concordance between risk assessment methods for three conditions tested in Navigenics PGT (breast cancer, prostate cancer, and colon cancer). We expand on their work by analyzing more conditions included in the PGT panel and in a larger sample of individuals.…”
Section: Family and Medical History Assessments: Other Potential Genesupporting
confidence: 92%
“…This is reflected by our finding that for the majority of the conditions, significantly more individuals were grouped into higher risk categories by PGT risk assessment (see Supplementary Table S1a,b online). For a more accurate comparison of risks between PGT and family history, further long-term studies should be undertaken looking at In summary, our data along with other studies 13,14 suggest that these two methods of risk assessment for common complex disorders provide different and perhaps complementary information. Our study provides one of the most extensive analyses to date of concordance between risk estimates provided by PGT and family history assessments and finds little to no concordance for 20 of the multifactorial conditions included in Navigenics PGT.…”
Section: Family and Medical History Assessments: Other Potential Genementioning
confidence: 70%
“…There are concerns that overstated claims create unrealistic consumer expectations, may harm privacy and induce confusion and anxiety. For example, one recent study 3 finds little concordance in results for cancer risk from personal genome screening and the family history-based risk assessment commonly used in genetic counselling services. There have been several initiatives by professional or advisory bodies to identify the issues for managing such tests, most notably by the European Society of Human Genetics (ESHG) 4 but also, for example, in the UK by the Human Genetics Commission 5 and in the United States by the American Medical Association.…”
mentioning
confidence: 99%
“…It is also important to note that, in spite of the excitement surrounding the genomic era, genetic prediction should not be given undue weight. Brandie et al [14] compared family history and genomic screening in the assessment of breast, prostate, or colorectal cancer risk, and concluded that genetic data is not a substitute for family history, and, in fact, family history remains the clinical standard.…”
Section: Genetic Versus Other Nongenetic Medical Informationmentioning
confidence: 99%